Training of Trainers (ToT) Pelatihan Webcommerce Ramah UMKM pada Dosen Anggota APBISDI Wilayah 8-9 (Bali, Nusa Tenggara, dan Indonesia Timur) - Syamsu Alam; Andi Ruslan; Andi Hermanto; Muh Jamil; Husni Mubarak (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service Program (PKM) aims to improve the competencies of E-Commerce lecturers affiliated with APBISDI Region 8-9 through MSME-friendly webcommerce training. This activity is motivated by the technical competency gap among academics in teaching practical and affordable webcommerce platforms for micro, small, and medium enterprises (MSMEs). The method used is Training of Trainers (ToT) with an andragogical approach, comprising conceptual presentations, participatory workshops, and live demonstrations of building a Blogger-based digital store. The program was conducted online on May 14, 2026, involving 48 lecturers from 25 higher education institutions across Bali, Nusa Tenggara, and Eastern Indonesia. Evaluation results showed a significant competency increase, with 87.5% of participants (42 out of 48) successfully completing the digital store configuration independently, particularly in SEO-friendly catalog management and digital payment integration via bank transfer and QRIS. All participants (100%) also demonstrated readiness to integrate this knowledge into project-based Semester Learning Plans (RPS). The Training of Trainers approach is recommended as a science and technology dissemination model to create a multiplier effect in accelerating digital transformation and MSME economic independence across regions.